The Sheath Warrior Returns: Identity and Ideology of the Nation - Agustinus Rustanta; Evvy Silalahi (Indonesian Journal of Law and Economics Review, 2020)
This research focuses on non-verbal communication of sarong worn by Ma’ruf Amin as the candidate of Vice President of Republic Indonesia for the period of 2019-2024 who had been declared by the public election commission (KPU) on Junie 28, 2019. To analyze the meaning of sarong, the researchers use semiotics of Charles Sanders Peirce. The findings indicate that sarong denotatively means a piece of cloth which is sewn at its end to become a kind of tube to cover part of man’s body especially his stomach and below. Furthermore, sarong has very deep meaning, they are showing self-identity, local culture, the symbol of resistance to the culture of the west, it shows sincerity, complex way of thinking, flexibility, elegance, smart thinking, and excellent morality.